Textile Wastewater Treatment via Membrane Photocatalytic Reactor (MPR) Incorporated ZnO-Kaolin - Azman, Ahmad Rafiq (Journal of Advanced Mechanical Engineering Applications, 2024)
Improperly treated or discharged textile wastewater can have negative impacts on the environment, leading to the pollution of water bodies, disruption of ecosystems, and a reduction in biodiversity. This study investigated the effectiveness of MPR, which incorporates ZnO-kaolin, in treating textile wastewater. ZnO-kaolin photocatalyst was successfully produced and comprises selective elements using the precipitation method, and the physico-chemical properties were characterized by using Fourier transform infrared (FTIR) and x-ray diffractometers (XRD). This study involved parameters such as initial pH (pH 6, 7, 8), ZnO-kaolin dosage (0.05, 0.1, 0.15, and 0.2 g/L), and initial concentration (90, 95, and 100%). The study suggests that the initial pH level has a significant impact on the efficiency of ZnO-kaolin in treating wastewater. The optimal pH for the removal of pollutants was determined to be 8 based on the presented data. The best amount of ZnO-Kaolin to use for effectively lowering pollutants in wastewater is 0.1 g/L, as shown by the higher percentages of color, turbidity, TDS, conductivity, and COD. The results highlight the importance of the photocatalyst dosage in the effectiveness of the treatment process. The study suggests that the initial concentration of ZnO-Kaolin plays a crucial role in the effectiveness of the wastewater treatment process. The results highlight optimal concentrations of 95% for achieving desired reductions in color, turbidity, TDS, conductivity, and COD. This study presents significant potential for the textile industry to reduce environmental issues and move toward sustainability.